Using advanced materials of granular BRA modifier binder to improve the flexural fatigue performance of asphalt mixtures - Karami, M.; Nikraz, Hamid (2015)
© 2015 The Authors. Published by Elsevier Ltd. The objective of this research is to determine the effect on the flexural fatigue performance of asphalt mixtures of using granular Buton rock asphalt (BRA) modifier binder. A repeated flexural bending test under the controlled-strain mode of loading in accordance with Austroads AG:PT/T233 test method was conducted to examine fatigue behaviour of the BRA modified asphalt mixtures and the unmodified asphalt mixtures (as control mixtures) for a dense grading of 10 mm. Beam specimens were tested at the temperatures of 20°C and three different peak tensile strain (400, 600 and 800 µe) and used classical and energy-stiffness ratio approach to analyse fatigue life of the asphalt mixtures. According to the test results, the fatigue lifes of the BRA modified asphalt mixtures were higher than that for the unmodified asphalt mixtures at the test temperature and tensile strain. Moreover, based on the initial flexure stiffness and phase angle values, BRA modified asphalt mixtures showed more elastic and less viscous behaviour than unmodified mixtures.